Perkembangan Bahasa Melalui Metode Bercerita Boneka Jari Anak Usia 5-6 Tahun Di Taman Kanak-Kanak (TK) Islam Terpadu Subulussalam Samarinda - Heppy Liana; Ismainatun Chotimah; Yeni Aslina (BEduManagers Journal : Borneo Educational Management and Research Journal, 2025)
The aim of this research is (1) To find out the strategies teachers can use to stimulate the language development of children aged 5-6 years at the Subulussalam Integrated Islamic Kindergarten, (2) To find out what supports and inhibits the language development of children aged 5-6 years at the Subulussalam Integrated Islamic Kindergarten. The method used is descriptive qualitative research, with data collection techniques including observation, interviews and documentation used to present data and draw conclusions. The results of this study are that using the storytelling method with finger puppets as a medium can attract children's interest by actively participating, and the teacher acts as a facilitator. The conclusion from the results of this study is that language development in children aged 5-6 years at the Subulussalam Integrated Islamic Kindergarten is still not optimal in receptive language development. So it is necessary to have stimulation to improve children's language development, namely by using the storytelling method. Supporting factors for children's language development include frequently inviting children to talk and finger puppet materials that are easy to obtain. The obstacle is that parents pay less attention to their children and children lack focus. Through the storytelling method using finger puppets, by achieving learning objectives that are in accordance with the indicators of receptive language development in children aged 5-6 years, this study has shown that the storytelling method can improve the language development of children aged 5-6 years at the Subulussalam Integrated Islamic Kindergarten.